TEACHING ENGLISH TO FOOD AND BEVERAGE STAFF USING A ROLE-PLAY METHOD - Odellia Bunga Wijanarko; Kezia Christy Sandika; Fransisca Tyas Ayu Kinanthi (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2023)
This study is conducted to apply the role-play method in teaching English for Specific Purposes (ESP) specifically for teaching English to Food and Beverages staff at Melcosh Café so that they can handle foreign customers who visit the cafe. The steps that we take will be by Huang’s theory (2008), which are (1) deciding the teaching material, (2) selecting the situation and creating the dialogue, (3) teaching dialogue for role play, (4) having students practice the role play, (5) having students modify the situation and dialogue, and (6) evaluating and checking students' comprehension. To make them learn better and also get the best result, it is better to learn and train their English using role-play methods so that they get the feeling of serving foreign customers in real-life situations. The result of this study is the handbook which incorporates ESP principles and roleplay practice.